Pharmacokinetics of fleroxacin after multiple oral dosing in patients receiving regular hemodialysis. - Uehlinger, D E (1996)
The pharmacokinetic profile of fleroxacin was studied in eight noninfected patients receiving regular hemodialysis (four women and four men; mean age, 63 years; age range, 48 to 73 years). Dialysis clearances (mean +/- standard deviation) calculated from the amount of drug recovered in the dialysate exceeded those calculated from rates of extraction from plasma for fleroxacin (126 +/- 29 versus 73 +/- 11 ml/min) and its metabolite N-demethylfleroxacin (103 +/- 31 versus 72 +/- 15 ml/min) but not that for the metabolite fleroxacin N-oxide (100 +/- 25 versus 100 +/- 12 ml/min). Data were fitted to a two-compartment model over the total observation period of 8 days (six oral daily doses of 200 mg of fleroxacin on days 1 to 6 and hemodialysis treatments on day 1,3, and 6) by nonlinear mixed-effects modeling. The random variability of plasma fleroxacin concentrations was 13% about its prediction. The estimated metabolic clearance was 25 ml/min (coefficient of variation, 43%), and the calculated steady-state volume of distribution was 84 liters (coefficient of variation, 16%). The model was expanded for the two major metabolites by the addition of a two-compartment metabolite distribution. Formation clearances of N-demethylfleroxacin and fleroxacin N-oxide were estimated to be 54 and 33% of fleroxacin's metabolic clearance, respectively. The conclusions were as follows. Because of the slow metabolic clearance and intermittent dialysis treatment, steady-state conditions were not reached after 1 week of oral fleroxacin therapy, and there was relevant accumulation of fleroxacin as well as that of fleroxacin N-oxide in our patients with end-stage renal disease. We recommend that infected hemodialysis patients be treated with an initial oral dose of 400 mg of fleroxacin and then daily oral doses of 200 mg. One cannot recommend the treatment of this patient population with fleroxacin over prolonged time periods until more date about the levels of accumulation of fleroxacin and its metabolites in infected patients with renal disease are available.